A mild hand cleanser, alkyl ether sulphate supplemented with alkyl ether carboxylic acid and alkyl glucoside, improves eczema on the hand and prevents the growth of Staphylococcus aureus on the skin surface. (26th April 2016) - Fukui, S.; Morikawa, T.; Hirahara, M.; Terada, Y.; Shimizu, M.; Takeuchi, K.; Takagi, Y.
Abstract: Objective: Washing the hands using cleansers with antiseptic materials is the most popular method for hand hygiene and helps maintain health by preventing food poisoning and bacterial infections. However, repeated hand washing tends to induce eczema of the hand, such as dryness, cracking and erythema. Moreover, eczema on the hand leads to increased levels in Staphylococcus aureus ( S. aureus ) on the skin surface in contrast to expectations. Thus, mild hand cleansers which induce less eczema even with repeated washings are desired. Here, we evaluated the efficacy of a hand cleanser formulated with alkyl ether sulphate (AES), alkyl ether carboxylic acid (AEC) and alkyl glucoside (AG) that contains isopropyl methylphenol (IPMP) on skin symptoms and S. aureus levels. Methods: Eczema of the hand and the presence of S. aureus on the skin surface were analysed prior to and following 4 weeks of usage of the hand cleanser. A soap‐based hand cleanser with IPMP was used as a reference cleanser. Eczema and cutaneous conditions were evaluated by visual grading, transepidermal water loss (TEWL), stratum corneum moisture‐retention ability (MRA) and skin surface pH. Results: The repeated use of the soap‐based hand cleanser significantly worsened the hand dryness, scaling and cracks on the tips of the fingers and significantly increased the TEWL and decreased the MRA. In contrast, usage of the test cleanser only induced a significant increase in skin dryness but did not induce skin scaling or cracking and did not increase TEWL or decrease the MRA. Corresponding to these changes in skin symptoms, the presence of S. aureus increased the following use of the reference cleanser but not the test cleanser. There was no significant difference in skin surface pH between the two cleansers. Moreover, the increase in S. aureus was significantly correlated to the worsening of skin dryness and scaling. Conclusion: These results suggest that not only antimicrobial activity but also the mildness, which minimizes cutaneous effects, are important for hand cleansers to prevent the growth of S. aureus . The cleanser formulated with AES, AEC and AG containing IPMP is mild and is effective to promote hand hygiene.